Multiple airy beams light-sheet fluorescence microscopy - Gu, Shuangyu; Yu, Xianghua; Bai, Chen; Min, Junwei; Li, Runze; Yang, Yanlong; Yao, Baoli (Frontiers in Physics, 2022)
Light-sheet fluorescence microscopy (LSFM) is a kind of volumetric imaging methodology suited for long term living specimens at high temporal-spatial resolution. A single Airy beam (SAB) light-sheet can extend the field of view of LSFM benefiting from its non-diffracting nature, but at the cost of out-of-focus background and low imaging contrast caused by side lobes illumination. Here, we propose a method to generate a sort of multiple Airy beams (MAB), which are linearly superimposed of multiple single Airy beams with different scale factors. Compared to the SAB light-sheet, the energy of the MAB light-sheet is more concentrated on the focal plane of the detection objective, which can improve the imaging contrast and decrease the photodamage effect. Furthermore, we combined the complementary beam subtraction (CBS) strategy to increase the axial resolution, termed as MAB-CBS method, which enables the axial resolution of 1.2 μm while keeping the field of view of 450 μm×450 μm. The effectiveness of the method is demonstrated by imaging of fluorescent beads and aspergillus conidiophores.